Conflict and Resolution in Marriage Law: Seeking a Middle Ground Between Mandailing Customary Law and Islamic Law in Satumarga Ritonga Marriages in Tanjung Medan Village, Labuhan Batu - Ritonga, Muhammad Alfarizi; Mukhsin, Abd. (Islamic Family Law Department, STAI Syekh Abdur Rauf Aceh Singkil, Indonesia, 2025)
The view of Ritonga's semarga marriage in Tanjung Medan Village, West Bilah District, Labuhan Batu Regency, with a focus on the perspectives of religious and traditional leaders. customary figures. The purpose of this research is to understand how Ritonga's semarga marriage is carried out, the views held by religious and traditional Ritonga's semarga marriage is carried out, the views held by religious and traditional leaders, and determining the more religious and traditional leaders, as well as determining which opinion is stronger and relevant to the current state of society. the current state of society. The method used in this research is a qualitative method with a sociological and normative-empirical approach. sociological and normative-empirical approaches. Data collection was conducted through interviews and documentation, while data analysis was carried out using the comparative method to evaluate the differences in views between religious and traditional leaders. to evaluate the differences in views between religious and traditional leaders. Findings revealed significant differences in views between religious and traditional leaders. Religious leaders state that surname marriage Ritonga's semarga marriage is permissible because there is no prohibition in Islamic teachings, while traditional leaders oppose it because it is considered contrary to customary norms and will be subject to customary sanctions. subject to customary sanctions. The opinion that is stronger and more relevant to the situation is the view of religious leaders, because it is in with Islamic law. [Pandangan terhadap perkawinan semarga Ritonga di Desa Tanjung Medan, Kecamatan Bilah Barat, Kabupaten Labuhan Batu, dengan fokus pada perspektif tokoh agama dan tokoh adat. Tujuan dari penelitian ini adalah untuk memahami bagaimana perkawinan semarga Ritonga dilaksanakan, pandangan yang dipegang oleh tokoh agama dan tokoh adat, serta menentukan pendapat yang lebih kuat dan relevan dengan keadaan masyarakat saat ini. Metode yang digunakan dalam penelitian ini adalah metode kualitatif dengan pendekatan sosiologis dan normatif-empiris. Pengumpulan data dilakukan melalui wawancara dan dokumentasi, sementara analisis data dilakukan dengan metode komparatif untuk mengevaluasi perbedaan pandangan antara tokoh agama dan tokoh adat. Temuan penelitian mengungkapkan adanya perbedaan pandangan yang signifikan antara tokoh agama dan tokoh adat. Tokoh agama menyatakan bahwa perkawinan semarga Ritonga diperbolehkan karena tidak ada larangan dalam ajaran Islam, sementara tokoh adat menentangnya karena dianggap bertentangan dengan norma adat dan akan dikenai sanksi adat. Pendapat yang lebih kuat dan relevan dengan situasi masyarakat saat ini adalah pandangan tokoh agama, karena sesuai dengan hukum Islam].